Electrical Conductivity Properties of Polyvinyl Alcohol: Graphene Nanocomposites - Wageh, S.; Al-Ghamdit, Ahmed A.; Al-Turki, Yusuf; Tjong, S. C.; El-Tantawy, Farid; Yakuphanoğlu, Fahrettin (Amer Scientific Publishers, 2014)
For the first time, the polyvinyl alcohol: graphene oxide nanoconnposite films for various contents of graphene oxide nanosheets were prepared by spin coating method. The synthesized GO nanosheets and PVA/GO nanoconnposites were characterized using field emission scanning electron microscope (FETEM) technique and energy dispersive X-ray spectroscopy (EDS). The electrical conductivity and current voltage characteristics of PVA/GO nanocomposites were investigated. The nanocomposites were underwent a transition from insulator to semiconductor behavior with GO content. The electrical characterization of Al/PVAGO/p-Si/Au diode was investigated by means of current voltage and capacitance voltage measurements. The prepared Al/PVAGO/p-Si/Au diodes exhibited the rectifying behavior and the rectifying properties were changed with GO content. Considering the very simple and effective fabricate process, the Al/PVAGO/p-Si/Au diodes are competitive candidate for several electronic applications.
Keywords: Graphene Oxide; Polyvinyl Alcohol Nanocomposites; Microstructure; Electrical; Diode